A heuristic approach to stochastic cutoff grade optimization for open pit mining complexes with multiple processing streams - Asad, Mohammad Waqar Ali; Dimitrakopoulos, Roussos (Resources policy, 2013)
Cutoff grade specifies the available supply of metallic ore from an open pit mine to the multiple processing streams of an open pit mining complex. An optimal cutoff grade strategy maximizes the net present value (NPV) of an open pit mining operation subject to the mining, processing, and marketing/refining capacity constraints. Even though, the quantities of material flowing from the mine to the market are influenced by the expected variation in the available metal content or inherent uncertainty in the supply of ore, the majority of cutoff grade optimization models not only disregard this aspect and may lead to unrealistic cash flows, but also they are limited in application to an open pit mining operation with single processing facility. The model proposed herein determines the optimal cutoff grade policy based on a stochastic framework that accounts for uncertainty in supply of ore to the multiple ore processing streams. An application on a large-scale open pit mining operation develops a unique cutoff grade policy along with a portfolio of mining, processing, and marketing/refining rates. Owing to the geological uncertainty, the approach addresses risk by showing a difference of 14% between the minimum and maximum production rates, cash flows and NPV. •Cutoff grade optimization model for an open pit mining complex considering geological uncertainty and multiple processing streams.•The model maximizes net present value and satisfies mine, processes, and market/refinery capacity constraints.•The model develops a unique cutoff grade policy under uncertain ore supply considering multiple simulated realizations of grade–tonnage curves.•The optimal cutoff grade policy is risk quantified for metal production rates and cash flows for life of operation.•A realistic application proves that low-grade and highly variable mineral resources are subject to higher risk under geological uncertainty.